Fogueira Santa de Israel e o consumismo religioso - Silveira Neto, Harry Carvalho da (2014)
The proposal of this dissertation was to make a reflection on religious consumerism is a historical process and is even more present nowadays in one of the most showy scenario Brazilian neo-churches, the UCKG. We analyze the process of symbolic exchanges inside of an event that has the same as flagship of their deals donation campaigns in Exchange for blessings, the Holy Fire of Israel. Furthermore we seek to understand the content and operation of your speeches of prosperity theology, which lined the right the conquest of wealth and material possessions through the sacrifices financial donations made in the name of faith. Our overall objective was: analyzing the testimonies of the faithful participants of campaigns the fire Santa of Israel of the IURD, with lines about the expressions of hope and success in attendance, as well as, the symbolisms expressed in most recurrent reports of the frustrations and disappointments of the participants who have not obtained answers to the sacrifices made by them. For this harvest, through secondary data and the Internet, the speeches of hope while expectations of care of the requests made by the faithful, as well as the frustration and disappointment that the faithful feel when they are not met within in these campaigns. The main theorists that inspired this research were: Lipovetsky (2007 and 2007), Bauman (2008), Baudrillard (1995 and 2000), Eliade (1992), Debord (1997), Kehl (1995)